Unconscious patient - role and tasks of the therapeutic team - Katarzyna Tomaszewska; Katarzyna Gronowska (Kazimierz Wielki University, 2020)
Unconscious patients are not able to decide for themselves whether to cooperate effectively with the medical personnel. That is why it is so important for all members of the therapeutic team to work together in a comprehensive way. Purpose of the research: Defining the role and tasks of the members of the therapeutic team caring for the unconscious patient in the intensive care unit. Materials and methods: The study involved 103 persons (79 women and 24 men). The study group consisted of nurses, doctors, physiotherapists and paramedics who work in Anaesthesiology and Intensive Care Units. A questionnaire of our own authorship was used for the research. Results and conclusions: Good communication between the members of the therapeutic team, respect and good relations with the superior do not affect the effectiveness of work according to the respondents. A clear division of duties between the members of the therapeutic team influences the quality of care for unconscious patients, which is significantly different from the care for conscious patients. The members of the therapeutic team know the methods of care, nutrition, rehabilitation of unconscious patients.